2014
DOI: 10.1007/s12032-014-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism rs41736 located in MET was significantly associated with prognosis of small cell lung cancer patients

Abstract: MET has been suggested to have an intimate relationship with small cell lung cancer (SCLC) and might be a promising therapeutic target. To date, relatively limited reports have been explored on MET mutational status in SCLC patients. To investigate the relationship between MET mutations and SCLC, 68 Chinese patients surgically treated for SCLC were enrolled. MET mutational analyses were performed in tumors, adjacent normal tissues as well as in lymph nodes with no metastasis nonadherent to tumor tissues using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Single-nucleotide polymorphism is the third generation of molecular markers of genetic variation, which is mainly used to study the differences in susceptibility of disease and sensitivity to different medication and treatment methods. To date, studies on relationship between lung cancer and SNPs mainly focused on NSCLC, and not much on SCLC (Knoefel et al, 2011;Gu et al, 2012;Szondy et al, 2012;Cao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphism is the third generation of molecular markers of genetic variation, which is mainly used to study the differences in susceptibility of disease and sensitivity to different medication and treatment methods. To date, studies on relationship between lung cancer and SNPs mainly focused on NSCLC, and not much on SCLC (Knoefel et al, 2011;Gu et al, 2012;Szondy et al, 2012;Cao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ueki et al found that HCC patients with high MET expression had a shorter 5-year survival than those with low MET expression [20]. Recently variants in MET have been reported to be associated with the prognosis of various human cancers, such as lung cancer and gastric cancer [30, 31]. Cao [30] et al found that compared with small cell lung cancer (SCLC) patients who carried the CT/TT genotypes of MET rs41736, those SCLC patients who carried the wild-genotype CC tended to have a shorter progression-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%